Anti-inflammatory effects of moxifloxacin and levofloxacin on cadmium-activated human astrocytes: Inhibition of proinflammatory cytokine release, TLR4/STAT3, and ERK/NF-κB signaling pathway - Suttinee Phuagkhaopong; Jidapha Sukwattanasombat; Kran Suknuntha; Christopher Power; Piyanuch Wonganan; Pornpun Vivithanaporn (PLoS ONE, 2025)
Cadmium is a non-essential element and neurotoxin that causes neuroinflammation, which leads to neurodegenerative diseases and brain cancer. To date, there are no specific or effective therapeutic agents to control inflammation and alleviate cadmium-induced progressive destruction of brain cells. Fluoroquinolones (FQs), widely used antimicrobials with effective blood-brain barrier penetration, show promise in being repurposed as anti-inflammatory drugs. Therefore, we aimed to test the efficacy of repurposed FQs for the treatment of cadmium-induced inflammation using cultures of U-87 MG human astrocytes and primary human astrocytes. Both FQs abrogated cadmium-induced interleukin (IL)-6 and IL-8 release from human astrocytes in a concentration and time-dependent manner, although levofloxacin had a stronger inhibitory effect than moxifloxacin. The downregulation of inflammatory cytokine release occurred with a concomitant reduction in cadmium-induced elevations in p65 nuclear factor-κB (NF-κB) and extracellular signal-regulated kinases (ERKs) 1/2 phosphorylation. Additionally, levofloxacin treatment significantly alleviated cadmium-induced activation of phosphorylated NF-κB translocation and toll-like receptor (TLR)-4/signal transducer and activator of transcription (STAT) 3 signaling. Transcriptome analysis revealed that modulation of inflammation-related pathways was the most enriched after FQ treatment. Our data suggest that FQs, particularly levofloxacin, attenuate the inflammatory process mediated by cadmium in human astrocytes. These effects may be mediated, at least in part, by inhibition of immune pathways regulated by TLR4, STAT3, ERK MAPK, and NF-κB.